Develop a framework for engineering change management in an aircraft manufacturing company - Zhu, Lin (Cranfield University, 2014)
The purpose of this research project is to develop a framework for engineering change management (ECM) in an aircraft manufacturing company. ECM is vital for manufacturers to manage changes efficiently and effectively. As an effective change control technique, ECM has been widely practiced in different industrial sectors. However, adopting an ECM process does not always guarantee the agility of the manufacturing process of the manufacturer. The performance of ECM could be affected by the actual practice followed by the ECM practitioner. The research was conducted in four phases. In the first phase an extensive literature review was carried out to understand the critical success factors related to the ECM and Configuration Management (CM) activities. The second phase was to model the current ECM practice in the aircraft manufacturing company by using IDEF0 approach. The actual ECM practice was understood and some gaps were identified in this part. In the third phase, a survey was carried out to identify the best practices in aerospace and automobile companies. A list of best practices that could promote the performance of the ECM was identified by analysing the result of the survey. In the last phase of the research, a framework was developed from the model of current ECM process in the company. The best ECM practices identified in the third part of the research were integrated into the model to refine the current ECM process. The framework was validated by experts in the aircraft manufacturing company. The outcome of this research shows the correlation between the performance of the ECM process and the actual ECM practices. And the framework developed in this thesis can provide benefits for the further improvement of the current ECM process in the aircraft company. The framework also offers a benchmarking reference for other companies with a similar background to examine their own ECM process and initiate improvement.
Keywords: Engineering change management; Configuration management; aircraft